2009
DOI: 10.1002/pola.23455
|View full text |Cite
|
Sign up to set email alerts
|

Random and sequential radical cotelomerizations of 3,3,3‐trifluoropropene (H2CCHCF3) with vinylidene fluoride (F2CCH2)

Abstract: The synthesis of original co-telomers based on 3,3,3-trifluoropropene (TFP) and vinylidene

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
26
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 21 publications
(29 citation statements)
references
References 54 publications
3
26
0
Order By: Relevance
“…Actually, the released bulky perfluorinated alkene (Scheme 1) is too hindered to undergo any radical (co)polymerization with styrene or trifluoromethyl styrene, as evidenced by the absences of the signals at ca. −82 and −78 ppm assigned to CF 3 end‐groups in CF 3 CF 2 and CF(CF 3 ) 2 , respectively [54] and that of CF(CF 3 ) 2 expected at −184 ppm [54] . In addition, our results confirm the absence of any trifluoromethylation of the benzylic side of toluene as reported by Sato et al [43] …”
Section: Resultssupporting
confidence: 88%
“…Actually, the released bulky perfluorinated alkene (Scheme 1) is too hindered to undergo any radical (co)polymerization with styrene or trifluoromethyl styrene, as evidenced by the absences of the signals at ca. −82 and −78 ppm assigned to CF 3 end‐groups in CF 3 CF 2 and CF(CF 3 ) 2 , respectively [54] and that of CF(CF 3 ) 2 expected at −184 ppm [54] . In addition, our results confirm the absence of any trifluoromethylation of the benzylic side of toluene as reported by Sato et al [43] …”
Section: Resultssupporting
confidence: 88%
“…We have found that r VDF = 1.20 ± 0.50 and r BDFE = 0.40 ± 0.15 at 75 °C showing that VDF is more reactive than BDFE and showing also that they are statistic copolymers as most of the copolymers of VDF 7. (a), 8 (c), 35–57 Compared with the reactivity ratios of other fluoromonomers able to copolymerize with VDF (Table 4), the value of the reactivity ratio of BDFE was found to be between that of HCFCF 2 (0.50) and that of F 2 CCF(CH 2 ) 3 SAc (0.41) (Table 4) but r VDF is much lower ( r VDF = 0.70 or 0.60, respectively vs. 1.20 in that present study). These values can be compared with the reactivity of other fluoromonomers able to copolymerize with VDF (Table 4),7 (a), 8 (c), 35–57 and with the values arising from the radical copolymerization of TFE with BDFE ( r TFE = 0.82; r BDFE = 0.24) 20…”
Section: Resultsmentioning
confidence: 83%
“…We considered R 0 as the ratio of the initial CTA concentration to the initial overall VDF concentration (i.e., the total VDF initial moles by volume of the liquid phase) [ 36 ]. …”
Section: Resultsmentioning
confidence: 99%
“…We considered R0 as the ratio of the initial CTA concentration to the initial overall VDF concentration (i.e., the total VDF initial moles by volume of the liquid phase) [36]. David and Gosselain's law [33] enabled us to assess the transfer constant to 2-mercaptoethanol of 40 at 140 °C.…”
Section: Kinetics Of Radical Telomerisation Of Vdf With 2-mercaptoethanolmentioning
confidence: 99%